Shakespeare’S Superiority Over His Contemporaries: Unraveling the Secrets of Shakespeare's Success (Journal of Advances and Scholarly Researches in Allied Education, 2014)
William Shakespeare is considered as one of the mostrenowned writers of the Elizabethan age. The greatest of all ElizabethanDramatists was Shakespeare in whose hands the Romantic drama reached itsclimax. As we do not know much about his life, and it is certain that he didnot have proper training and education as other dramatist of the period had,his stupendous achievements are an enigma to all scholars up to the presentday. The present research paper attempts to present the main features ofShakespeare’s plays which account for his superiority over his contemporaries.